Iowa Birdline update, September 26-30, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for September 26-30, 1988. Highlights of the update include sightings of two rare birds, a Magnificent Frigatebird and a Pomarine Jaeger. Also of note were the observations of numerous American White Pelicans and Ospreys as well as sightings of several species of Hawks, Warblers, and shorebirds. Epson - sheet feed